2019
DOI: 10.1111/desc.12905
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers find ways to resist temptation after learning that willpower can be energizing

Abstract: Children's tendency to delay gratification predicts important life outcomes, yet little is known about how to enhance delay of gratification other than by teaching task‐specific strategies. The present research investigated the effect of exposing children to a model who experiences the exertion of willpower as energizing. In two experiments, 86 4‐ to 5‐year olds were read a story that represented the exertion of willpower as energizing or a control story before taking part in a delay of gratification task. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 76 publications
(94 reference statements)
2
28
0
Order By: Relevance
“…Over the last decades, Dweck and colleagues (Dweck and Leggett, 1988;Mueller and Dweck, 1998;Gunderson et al, 2013;Haimovitz et al, 2019) have shown that children develop implicit theories about their abilities as being either fixed (fixed mindset) or capable of growing (growth mindset) based on experiences such as praise and feedback for success and failure. Children with a growth mindset show better behavioral self-regulation, as they embrace challenges as learning opportunities to grow and improve their abilities (Molden and Dweck, 2006;Burnette et al, 2013;Compagnoni et al, 2019).…”
Section: Self-regulation In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decades, Dweck and colleagues (Dweck and Leggett, 1988;Mueller and Dweck, 1998;Gunderson et al, 2013;Haimovitz et al, 2019) have shown that children develop implicit theories about their abilities as being either fixed (fixed mindset) or capable of growing (growth mindset) based on experiences such as praise and feedback for success and failure. Children with a growth mindset show better behavioral self-regulation, as they embrace challenges as learning opportunities to grow and improve their abilities (Molden and Dweck, 2006;Burnette et al, 2013;Compagnoni et al, 2019).…”
Section: Self-regulation In Childrenmentioning
confidence: 99%
“…Since only one study has examined the correlates of willpower theories in young children (Haimovitz et al, 2019), there is a paucity of research examining the role that willpower theories play in explaining early selfregulation. Haimovitz et al (2019) found that children with experimentally induced non-limited theories (through a model in a storybook who experiences exerting willpower as energizing) showed more self-control strategies in the face of temptation, spent more time on the strategies, and showed longer delay of gratification than the group of children with a experimentally induced limited theory. The results imply that diverse behavioral self-regulation may develop not just as a set of skills learned through repeated practice on challenging tasks, as examined in past research (Diamond and Lee, 2011).…”
Section: Willpower Theories As Predictor Of Behavioral Self-regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an under-explored but common feature of self-control exertions admitting of individual variation (Ford et al, 2019) . During marshmallow studies, children attempt strategy switches in varying degrees, and those who make more distinct attempts and try more diverse strategies tend to have greater success at delaying gratification (Carlson & Beck, 2008;Haimovitz et al, 2019) . The job of agentive guidance thus continues while self-control exertion lasts, and often requires attempting multiple strategies in a single episode.…”
Section: Skillful Guidance During Self-control Exertionmentioning
confidence: 99%
“…These findings have been robust across studies in the laboratory and classroom (Ramani and Siegler, 2008;Siegler and Ramani, 2009;Ramani et al, 2012), supporting the use of board games in interventions with preschool children. While no study has used a board game to promote DG specifically, more traditional approaches promoting this and related selfregulation skills have highlighted key facets of successful interventions, including that these skills are more likely to be improved when: (1) they are modeled by others (Corriveau et al, 2016;Haimovitz et al, 2019;Munakata et al, 2020);…”
Section: Introductionmentioning
confidence: 99%